The Consumer Preference to the Beef Product at Traditional Market in Semarang City - Fakhrana Nurdini Cantika; Edy Prasetyo; Agus Setiadi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
As we know, the most important human need is food. Nowadays, many people awared that food with high nutrition is one of the welfare indicators in the society. Beef is animal food commodity from livestock that has high nutritional value. The aims of this research were to analyze the characteristic and consumers’ preference to the beef at traditional market in Semarang City. The researcher chose Semarang City as the research location based on purposive method. The sample was randomly chosen, of 100 respondents based on the quota sampling technique. Meanwhile, the taking sample method that used was purposive sampling method. This research used some data analysis, which were descriptive analysis, chi square analysis, crosstab analysis and conjoin analysis. Based on the research result, it conducted that most of the consumer characteristic was female, 36 – 40 years old, graduated from Senior High School, worked as housewife and have family income of > Rp. 5.000.000 per month. There was a connection between the number of family member and the number of beef purchase. The consumers more preferred bright red beef, without fat and beef cut of the part 3 (shank, rib, flank and brisket). The sequences of beef from the most important part based on Importance Values was 44,99% of fat, 28,24% of the color and 26,75% of the cut.